Wartościowanie w komentarzach redaktorów TVP Kultura po występach uczestników XVIII Międzynarodowego Konkursu Chopinowskiego w 2021 r. = Evaluation in the comments of the editors of TVP Kultura after the performances of the participants of the XVIII International Chopin Competition in 2021 - Kładoczny, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the evaluations of musical performances of young pianists as part of the XVIII International Chopin Competition in 2021 in Warsaw presented during the competition studio at TVP Kultura. To describe these performances and evaluate them, the editors and invited experts used linguistic means typical of aesthetic, general vital and cognitive evaluation.
Keywords: Konkurs Chopinowski; wartościowanie w języku; synestezja; metafora; muzyka w języku; Chopin Competition; evaluation in language; synesthesia; metaphor; music in language